2016
DOI: 10.1186/s12969-016-0109-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic recurrent multifocal osteomyelitis (CRMO) – advancing the diagnosis

Abstract: BackgroundChronic recurrent multifocal osteomyelitis (CRMO) is a little known inflammatory bone disease occurring primarily in children and adolescents. Delays in referral and diagnosis may lead to prolonged courses of antibiotics with in-patient care, unnecessary radiation exposure from multiple plain radiographs or bone scans and repeated surgery including bone biopsies.Children (aged < 18 years) diagnosed with CRMO between January 2005 and December 2012, reviewed at Bristol Royal Hospital for Children were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
219
5
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(250 citation statements)
references
References 8 publications
11
219
5
15
Order By: Relevance
“…Diagnosis of CRMO was then confirmed by a specialist from tertiary hospital on bone biopsy of lytic lesions. Discussion CRMO is an uncommon diagnosis, cases are reported to have months to years' time interval between presentation to diagnosis (2). Through this case, we aim to raise awareness amongst clinicians to shorten time to make diagnosis and to avoid unnecessary admissions.…”
Section: P35mentioning
confidence: 94%
“…Diagnosis of CRMO was then confirmed by a specialist from tertiary hospital on bone biopsy of lytic lesions. Discussion CRMO is an uncommon diagnosis, cases are reported to have months to years' time interval between presentation to diagnosis (2). Through this case, we aim to raise awareness amongst clinicians to shorten time to make diagnosis and to avoid unnecessary admissions.…”
Section: P35mentioning
confidence: 94%
“…Score values between 29-38 were indeterminate and require close clinical monitoring 18 also created the Bristol diagnostic criteria based off a cohort study from children diagnosed with CRMO at Bristol Royal Hospital for Children to reduce delay in diagnosis. 19 Based off this criteria, CNO can be diagnosed with the 1) presence of typical clinical findings, 2) the presence of typical radiological findings and either 3)>1 bone lesion with CRP<30 g/L or 4) unifocal disease and/or CRP>30 with negative bacterial growth on bone biopsy, 19 (Figures 1-4). c. Figure 4C: Axial T1 shows cortical thickening and bone marrow edema.…”
Section: Clinical Features/workupmentioning
confidence: 99%
“…20 While patients may initially present with a single site of painful bone involvement, studies have shown that patient have, on average, ~3.5 bony lesions. [15][16][17][18][19][20][21] To evaluate these silent lesions, bone scintigraphy and/or whole-body MRI are used. Bone scintigraphy uses Technetium 99 m to identify areas of bone remodeling.…”
Section: Image Findingsmentioning
confidence: 99%
“…Chronic nonbacterial osteomyelitis (CNO) is an autoinflammatory bone disease, which may evolve to bony destruction and deformity. The diagnosis of CNO is based on clinical bone pain, lytic and/or sclerotic bone lesion by radiography, and/or edema on magnetic resonance imaging (MRI) once malignancy and infection have been excluded . The disease is most common in long bones .…”
Section: Introductionmentioning
confidence: 99%